How to Improvise Medical Conferences - Vishnu Sharma (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Over the past few years, the number of attentive audience in medical conferences is steadily on the decline. Now information can be gathered easily from multiple sources. Hence, very few are interested to hear the routine lectures in medical conferences. Probably now, it is time to replace the routine lectures with interactive sessions with active participation from the audience. The scientific sessions and topics should be relevant, practical and should arouse the interest and enthusiasm among the delegates to attend the sessions. Carefully select the faculty who are subject experts having contribution with original work on the particular topic. Interactive sessions with experts, discussion of a clinical question/scenario, case discussions, year in review, debates on hot topics, self-assessment sessions, meeting the mentor sessions, expert group discussions & collaboration can be planned to replace the routine lectures. Dedicated sessions for trainees/postgraduates can be held. an expert panel can discuss and come out with at least two important conference resolutions which can be publicized as the conference outcome.